Proppant embedment in rough fractures considering shale hydration - Cong Lu; Qijun Zeng; Jiaxing Liu; Zhenfu Ma; Xianzhen Shao; Lin Tang; Yanxia Huang; Guangqing Zhou; Xianbo Meng; Jiandong Wang; Jianchun Guo (Energy Reports, 2023)
Shale reservoirs are significantly hydrated owing to the presence of large amounts of clay minerals. However, the mechanical properties of the hydration layer on the rock surface decline, resulting in severe proppant embedding. In this study, we established a mathematical model of proppant embedding based on the rock surface indentation experiment and Hertz contact theory, carried out shale spontaneous imbibition experiments to develop a mathematical model for the hydration depth, and built a proppant embedded mathematical model of rough fractures considering the elastic–elastoplastic–plastic whole-stage. We analyzed the proppant embedding laws by considering the hydration layer under closing stress. Our observations were as follows: the surface mechanical properties of hydrated shale decreased by 35.7% after 15 days of hydration intrusion; spontaneous imbibition water absorption in horizontal bedding was greater than that in the vertical bedding; the degree of proppant embedding increased with the increase in shale hydration time. As the closing stress increased, the degree of proppant embedding in the slick water liquid shale became significantly weaker than that in the distilled water liquid shale. This research provided a theoretical basis for shale reservoir fracturing design and fracture effectiveness analysis after fracturing.